Trends in incidence and survival from anal cancer and incidence of high-grade anal intraepithelial neoplasia in Denmark. (April 2022) - Urbute, Aivara; Munk, Christian; Sand, Freja L.; Belmonte, Federica; Kjaer, Susanne K.
Abstract: Objective: The aim of the current study was to assess temporal trends in incidence of anal squamous cell carcinomas (SCC) and high-grade anal intraepithelial lesions (AIN2/3), and estimate survival from anal cancer and factors related to 5-year mortality in Denmark. Methods: We analyzed anal SCC and AIN2/3 cases in the period of 1998–2018 from the Danish Cancer Register and the Danish Registry of Pathology, respectively. Overall, period, gender, and histology specific age-standardized incidence rates, average annual percentage change (AAPC), and 5-year relative survival were estimated. Cox proportional hazards models were applied to evaluate the effect on 5-year mortality of period, age, gender, and stage of disease. Results: Altogether 2580 anal cancers and 871 AIN2/3 were identified. The AIN2/3 incidence increased for women 1998–2007 (AAPC: 3.5% (95% CI −0.7, 8.0)) and then tended to decrease during 2008–2018(AAPC: −5.2% (95% CI −9.6, −0.6)). A similar pattern was observed for men, although at a lower incidence with the decrease starting later (2008–2012) and the trend not reaching statistical significance. The anal SCC incidence increased over the whole study period for both women and men (women AAPC: 4.0% (95% CI 3.2%, 4.9%) and men AAPC: 3.6% (95% CI 2.3%, 4.9%)). The relative survival improved over time (from 61% to 72%). Being older and male was associated with a higher risk of dying within 5 years. Conclusions: There is a need to focus attention on anal cancer and its precursor lesions, as the cancer incidence continues to increase. Actions could include screening and gender-neutral HPV vaccination. Highlights: Incidence of anal precancers in women increased until 2007, and then tended to decrease. Incidence of anal squamous cell carcinoma increased during the period 1998–2018. Male sex and older age were associated with higher risk of dying from anal cancer.